Problematizing Māori achievement in education policy : an exploratory mixed-methods study on teacher enactment of Ka Hikitia : a thesis presented in partial fulfilment of the requirement for the degree of Doctor of Education at Massey University, Manawatū, New Zealand - Niwa, Timu-o-te-rangi (Massey University, 2022)
This thesis analyses and describes a range of factors that impact upon mainstream primary school teachers’ enactments of the Māori education policy strategy, Ka Hikitia (Ministry of Education, 2013, 2018, 2020). Where this study differs is that it goes beyond the traditional implementation approach to policy research and seeks to identify and investigate the ‘messier’ aspects of interpretation, subjectivity and context, factors that are often missing in accounts of how policy works in schools. It has utilised an exploratory, two-phase mixed-methods approach to collect the data. The initial phase was a series of one-to-one interviews with a small cohort of primary school teachers from the Manawatū region of New Zealand. The data collated helped to develop a set of initial themes that were used to formulate the second phase survey that was sent out to a wider cohort. The themes from both two phases of the study have been used in a complementary manner to engage with research and literature from the fields of Māori education, culturally responsive pedagogy and critical policy enactment. This study concludes that teachers rely heavily upon school context and personal subjectivities to interpret and enact Ka Hikitia. It contends that teachers respond to Ka Hikitia in three key ways: considered enactment, perfunctory enactment, and/or enactment resistance. While teacher enactment is a focus of this study, it is purported that a broader consideration of how government and institutional factors impact upon teacher enactment of Ka Hikitia needs to be taken into account. Solely focusing on teachers as mere ciphers of policy reinforces institutional invisibility. This study calls for a broader understanding of how Māori student achievement is understood and problematized in Ka Hikitia. While supporting the necessity for Māori language, culture and identity to be an integral part of mainstream primary schools, this research urges policy makers and Māori academics to re-consider and re-calibrate the impact of socio-economic factors upon Māori student achievement and, henceforth, rework policy designed to address this.
Keywords: New Zealand. Ministry of Education. Ka hikitia; Maori (New Zealand people); Education (Elementary); Education and state; Academic achievement; Elementary school teaching; New Zealand; Mātauranga; Kāwanatanga; Tamariki; Waihanga; Māori Doctoral Thesis; 390201 Education policy